THE OPENEHR ELECTRONIC MEDICAL RECORD IN CONTENT MANAGEMENT SYSTEMS: TOWARDS AN IMPLEMENTATION - Pessanha, Christiano Pereira (Seven Editora, 2024)
This article describes research motivated by the challenges arising from efforts that seek semantic interoperability in Electronic Health Records (EHR) via the OpenEHR standard. The research sought the implementation of OpenEHR information models in Python language, as these models provide the semantics necessary for the construction of OpenEHR archetypes. As a contribution, it implements and opens the perspective of expression of the OpenEHR Archetypes on this platform, suggesting the feasibility of implementing this pattern in the various language frameworks. The research analyzes the requirements involved in the implementation of the OpenEHR standard in RES software coded from scratch, verifying the various advantages of its implementation in CMS's. The result of this theoretical effort clarifies the possibilities of building this type of software in content management systems, in general.DOI: https://doi.org/10.56238/sevened2024.037-112